2007
DOI: 10.1007/s11745-007-3087-8
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Conjugated Linoleic Acid Consumption Does Not Influence Milk Macronutrient Contents in all Healthy Lactating Women

Abstract: The term "conjugated linoleic acid" (CLA) refers to a group of positional and geometric isomers that are derived from linoleic acid and are found primarily in meat and milk products from ruminant animals. Due to the array of putative benefits associated with various forms of CLA, there has been recent interest in supplementing human diets with these fatty acids especially when weight loss is desired. However, in many animal models, CLA has been shown to decrease milk fat production. There is some concern, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Reflex maturation Palm grasp 6.5 (5-9) 9 (8-11) 4 (3-8)* , ** Righting reflex 4 (3-6) 5.5 (2-10) 3 (1-6)* , ** Cliff avoidance 6 (3-9) 6 (2-9) 4 (1-6)* , ** Vibrissae placing 9.5 (8-11) 10 (7-11) 9 (6-11)** Negative geotaxis 14 (7-11) 14 (8-14) 10 (7-12)* , ** Auditory startle 12 (11)(12)(13) 13 (12)(13)(14)(15) 10.5 (9-13)* , ** Free-fall righting 18 (15)(16)(17)(18)(19)(20) 17 (14)(15)(16)(17)(18) 16 (13)(14)(15)(16)(17)*…”
Section: Goat Milk Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflex maturation Palm grasp 6.5 (5-9) 9 (8-11) 4 (3-8)* , ** Righting reflex 4 (3-6) 5.5 (2-10) 3 (1-6)* , ** Cliff avoidance 6 (3-9) 6 (2-9) 4 (1-6)* , ** Vibrissae placing 9.5 (8-11) 10 (7-11) 9 (6-11)** Negative geotaxis 14 (7-11) 14 (8-14) 10 (7-12)* , ** Auditory startle 12 (11)(12)(13) 13 (12)(13)(14)(15) 10.5 (9-13)* , ** Free-fall righting 18 (15)(16)(17)(18)(19)(20) 17 (14)(15)(16)(17)(18) 16 (13)(14)(15)(16)(17)*…”
Section: Goat Milk Lipidsmentioning
confidence: 99%
“…14 Analyzing breast milk from women receiving supplementation with CLA was observed in the milk the presence of CLA isomers but there were no modifications in the macronutrients composition. 15,16 Preliminary studies showed that dietary CLA offered to pregnancy and/or lactating rats are able to crossing the blood-brain barrier of the offspring and stay until a postnatal period. 17 However, it has been observed that an outcome of drinking goat milk (which CLA is included) versus cow's milk increased weight gain, length, and skeletal mineralization in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CLA-induced milk fat reduction has been observed in bovine, ovine, and murine species [6][7][8]. Similarly, we have reported that consumption of a preparation consisting mainly of two CLA isomers (c9,t11-and t10,c12-18:2) reduced milk fat concentration by 23% in a group of well-nourished women [9], although more recent work from our group does not appear to support this [10]. A reduction in milk fat percentage was also observed in lactating women consuming large amounts of a trans fatty acid-containing margarine in comparison to when they consumed diets containing large amounts of a low trans fatty acid margarine [11].…”
Section: Introductionmentioning
confidence: 59%
“…Due to the cross over design of the human study (CLA effect was not studied during the same period of lactation) and the low number of subjects, the relevance of such a finding is unclear. More recent studies performed either with CLA mixtures (Mosley et al, 2007; 50:50 CLA 2 or 4 g per day) in 36 lactating women or with pure isomers in 12 lactating women (Hasin et al, 2005; 750 mg per day of each isomer) showed no effect on milk composition.…”
Section: Impact On Milk Secretion and Contentmentioning
confidence: 94%